What a wonderful world - Thiele, Bob 1922-1996; Weiss, George David 1921-2010 (Henry Holt and Company, 2014)
Illustrations and lyrics introduce a song, first recorded in 1967 by Louis Armstrong, which celebrates the wonders of nature, loving friends, and the promise of the future in a baby's cry
"First published in hardcover in 2014 by Oxford University Press."
Sänger auf dem Schutzumschlag
Keywords: JUVENILE FICTION / Performing Arts / Music; Musik; Children's songs, English -- United States -- Texts; Songs; Nature; USA; Bilderbuch